2020
DOI: 10.1523/eneuro.0107-20.2020
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous Opsin 3 (OPN3) Protein Expression in the Adult Brain Using a Novel OPN3-mCherry Knock-In Mouse Model

Abstract: The opsins have been studied extensively for their functions in visual phototransduction; however, the mechanisms underlying extraocular opsin signaling remain poorly understood. The first mammalian extraocular opsin to be discovered, opsin 3 (OPN3), was found in the brain more than two decades ago, yet its function remains unknown. A significant hindrance to studying OPN3 has been a lack of specific antibodies against mammalian OPN3, resulting in an incomplete understanding of its expression in the brain. Alt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 57 publications
2
11
0
Order By: Relevance
“…Notably, our study identified 25 new Opn3 -eGFP + structures in the CNS and PNS, including sensory ganglions, the olfactory epithelium, vestibular nuclei and parafascicular nucleus, that have not been previously reported to express Opn3 ( Table 1 ). The analyzed Opn3 -eGFP knock-in mouse line possesses two intact Opn3 wild-type alleles that are consistent with an observed normal phenotype, which is in contrast to the recently developed Opn3::mCherry fusion protein mouse line ( Olinski et al, 2020b ). Being under the influence of the native Opn3 promoter, both detected eGFP and Opn3::mCherry expression patterns appear to mirror the cellular expression profile of endogenous Opn3 from earlier reports.…”
Section: Discussionmentioning
confidence: 81%
See 4 more Smart Citations
“…Notably, our study identified 25 new Opn3 -eGFP + structures in the CNS and PNS, including sensory ganglions, the olfactory epithelium, vestibular nuclei and parafascicular nucleus, that have not been previously reported to express Opn3 ( Table 1 ). The analyzed Opn3 -eGFP knock-in mouse line possesses two intact Opn3 wild-type alleles that are consistent with an observed normal phenotype, which is in contrast to the recently developed Opn3::mCherry fusion protein mouse line ( Olinski et al, 2020b ). Being under the influence of the native Opn3 promoter, both detected eGFP and Opn3::mCherry expression patterns appear to mirror the cellular expression profile of endogenous Opn3 from earlier reports.…”
Section: Discussionmentioning
confidence: 81%
“…Studies of adult Opn3::mCherry reporter mice have reported that Opn3 is expressed also in non-neuronal astrocytes ( Olinski et al, 2020b ). In mouse, the differentiation of astrocytes begins ∼E17–E18 ( Reemst et al, 2016 ; Matsue et al, 2018 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations